2020
DOI: 10.1002/biot.202000023
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Novel TALEN Targeting CCR5 Confirms Efficacy and Safety in Conferring Resistance to HIV‐1 Infection

Abstract: Therapies to treat patients infected with human immunodeficiency virus (HIV) aim at preventing viral replication but fail to eliminate the virus. Although transplantation of allogeneic CCR5Δ32 homozygous stem cell grafts provided a cure for a few patients, this approach is not considered a general therapeutic strategy because of potential side effects. Conversely, gene editing to disrupt the C‐C chemokine receptor type 5 (CCR5) locus, which encodes the major HIV coreceptor, has shown to confer resistance to CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Likewise, monitoring of T-cell proliferation after electroporation with or without TALEN revealed no differences. Together, this data supports that CCR5 editing has no influence on T-cell fitness, as described by other groups, as well [ 41 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Likewise, monitoring of T-cell proliferation after electroporation with or without TALEN revealed no differences. Together, this data supports that CCR5 editing has no influence on T-cell fitness, as described by other groups, as well [ 41 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…Higher editing efficiencies were possible but associated with substantially increased off-target activity at the highly similar CCR2 locus. Our editing rates are well in line with previous [ 18 ] and novel data [ 41 ] for selected, high-efficiency TALENs. In comparison to zinc finger nucleases, which were already tested in a clinical study, our CCR5-Uco-hetTALEN showed higher CCR5 -editing rates with better safety profile [ 40 , 42 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study put forward a broad prospect of using TALENS to generate site-specific, size-controlled, and homozygous DNA deletions within mammalian genomes. Additionally, after transferring TALEN-encoding mRNA into CD4+ T cells, the CCR5 alleles were disrupted by 90%, whereas the off-target activity was absent and the edited cells proliferated normally (30). As a result, TALEN-mediated CCR5 disruption of CD4+ T cells is paving the way for clinical applications in CD34+ HSCs.…”
Section: Transcription-activator-like Effector Nucleasesmentioning
confidence: 99%
“…Finally, the paper by Romito et al. [ 14 ] presents a viral vector‐free ex vivo gene therapy approach based on the use of electroporation in view of gene editing of primary CD4+ T cells for rendering them resistant to HIV‐1 infection (disruption of CCR5 alleles). In addition to the stable modification, the absence of mutagenic events was shown.…”
mentioning
confidence: 99%